RURAL HOUSEHOLD LIVELIHOOD DIVERSIFICATION, SUSTAINABLE POVERTY REDUCTION AND AGENCY: A STUDY OF SELECTED COMMUNITIES IN THE AGRICULTURAL ZONES OF IMO STATE, NIGERIA - Onyekwere, Iwundu Anthony; Kanu, Winifred Nwabuaku (African Journal of Social and Behavioural Sciences, 2022)
Diversification in rural livelihood activities has been the key to grassroots development in rural communities of Nigeria. The gains in outcome seem not to last long, either due to lack of sustainability or poor democratic agency. This study investigated these issues by a structured survey study. The study was based on 540households. The Rural Livelihood Adoption Framework formed the framework of the study. The objectives include: to identify the diverse livelihood activities in the rural communities; determine the movers of rural livelihood activities; associate the often reversed gains of livelihood measures to poor sustainability; associate the reversed gains of livelihood measures to weak democratic agency. Hypotheses were tested with correlation techniques. The findings include: the presence of diverse livelihood portfolios in the area surveyed; women were more pronounced than men in diversification of activities; the diversified portfolio impacted positively on poverty reduction but households quickly return to poverty; households have not been embracing sustainable strategies and they lacked agency for the sake of security, voice and protection. It is recommended that; households would bring more portfolio options and pursuit into their existing list; men should be motivated to embrace opportunities and strengthen the women; agency should be encouraged in the rural areas to check government arbitrary economic conduct; households would have to embrace proper sustainability agenda in order to avoid slip back to poverty.